A fatal case of Lucio phenomenon in untreated Lucio leprosy - Batubara, Irwan Saputra; Marissa, Melani; Menaldi, Sri Linuwih; Sujudi, Yufanti (Journal of Pakistan Association of Dermatologists, 2023)
Lucio phenomenon (LP) is a rare and potentially fatal reaction that exclusively occurs in diffuse lepromatous leprosy or Lucio leprosy. It is characterized by purpuric macules, which progressively develop into extensive painful ulceration, primarily affecting the lower extremities. We report a case of 56-year-old with purpuric patches, blisters, and erosions on his face, mouth, arms, hands, legs, and feet that started to appear for three days without any hypopigmented or erythematous patches prior to the complaint. Slit skin smear examination revealed a bacterial index of 6+ with a morphological index of 13.66% and the Ziehl-Neelsen stains for acid fast bacili (AFB) were positive. He was diagnosed with LP complicating with sepsis. He was managed with multidrug therapy for multi-bacilary leprosy, corticosteroid, and antibiotic. However, his clinical condition was deteriorated and he died due to septic shock. Early recognition and prompt management are the key to successful therapy and preventing complications. Until now, there is no standard guideline for LP treatment due to its rare incidence. Multi-drug therapy for multibacillary leprosy is recommended for the management of LP. The use of corticosteroids and thalidomide is still controversial.